Relationship between Parental Education and Food Consumption Diversity on Adequate Energy Intake - Suherlan, Suci Anugrah; Sefrina, Linda Riski; Elvandari, Milliyantri (Universitas Muhammadiyah Surakarta, 2025)
Pendahuluan: Pendidikan orang tua dan keragaman pangan diprediksi dapat memengaruhi angka kecukupan asupan energi pada usia anak sekolah dasar. Tujuan penelitian ini untuk mengetahui hubungan pendidikan orang tua dan keragaman pangan terhadap kecukupan asupan energi. Metode: Penelitian ini menggunakan 25 sampel siswa dan siswi Sekolah Dasar Negeri WADAS 1. Pengumpulan data dilakukan dengan menggunakan kuesioner, penelitian ini merupakan penelitian kuantitatif dengan pendekatan cross-sectional. Uji analisis yang digunakan dalam penelitian ini adalah uji analisis hubungan menggunakan uji rank spearman, karena data dinyatakan tidak terdistribusi normal. Hasil: Hasil penelitian menunjukkan tidak terdapat hubungan signifikan antara pendidikan orang tua dengan kecukupan asupan energi ditandai dengan (p = 0,486 > 0,05), dan tidak terdapat hubungan antara keragaman konsumsi pangan dengan kecukupan asupan energi ditandai dengan (p = 0,347 > 0,05). Kesimpulan: Kesimpulan dari penelitian ini yaitu tidak ada hubungan antara pendidikan orang tua dengan kecukupan asupan energi, dan tidak ada hubungan antara keragaman konsumsi pangan dengan kecukupan asupan energi. Peneliti selanjutnya dapat melakukan penelitian dengan jumlah responden yang lebih banyak dan dengan responden yang lebih beragam agar hasil penelitian lebih representatif dan dapat digeneralisasi. Introduction: Parental education and dietary diversity are predicted to influence the adequacy of energy intake in elementary school children. The purpose of this study was to determine the relationship between parental education and dietary diversity on the adequacy of energy intake. Method: This study used 25 samples of male and female students from WADAS 1 Public Elementary School. Research related to parental education was obtained from primary data using a socio-demographic questionnaire, and research related to the eating history of the research subjects using the Dietary Diversity Score (DDS) questionnaire. This study is a quantitative study with a cross-sectional approach. The analysis test used in this study was a correlation analysis test using the Spearman rank test, because the data were declared not normally distributed. Result: The results of the univariate study of energy adequacy based on education showed that education was not a determinant of adequate energy intake in children. Meanwhile, energy adequacy based on the diversity of food consumption illustrates that diverse foods cannot necessarily meet the energy intake requirements. The results of the bivariate study showed no significant relationship between parental education and adequate energy intake, indicated by (p = 0.486 > 0.05), and no relationship between the diversity of food consumption and adequate energy intake, indicated by (p = 0.347 > 0.05). Conclusion: The conclusion of this study is that there is no relationship between parental education and adequate energy intake, and there is no relationship between the diversity of food consumption and adequate energy intake. Further researchers can conduct research with a larger number of respondents and with more diverse respondents so that the research results are more representative and can be generalized.